2019
DOI: 10.1186/s12889-018-6349-x
|View full text |Cite
|
Sign up to set email alerts
|

Service-users’ perspectives of link worker social prescribing: a qualitative follow-up study

Abstract: BackgroundSocial prescribing enables health-care professionals to address non-medical causes of ill-health by harnessing the resources of the voluntary and community sectors in patient care. Although increasingly popular in the UK, evidence for the effectiveness of social prescribing is inconclusive and longer-term studies are needed. This study aimed to explore experiences of social prescribing among people with long-term conditions one to two years after their initial engagement with a social prescribing ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
190
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(193 citation statements)
references
References 18 publications
3
190
0
Order By: Relevance
“…However, the lack of robust evidence of effectiveness does not mean social prescribing is ineffective. Findings from qualitative studies suggest that patients are satisfied with social prescribing schemes, particularly valuing a trusting and supportive relationship with their link worker, the time and space to address social problems, and link workers’ extensive knowledge of the range of community support services available 14151617. Recent systematic reviews of non-clinical community interventions identified evidence, albeit weak, of a further range of patient benefits 1218.…”
Section: Is There Evidence That Social Prescribing Work?mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the lack of robust evidence of effectiveness does not mean social prescribing is ineffective. Findings from qualitative studies suggest that patients are satisfied with social prescribing schemes, particularly valuing a trusting and supportive relationship with their link worker, the time and space to address social problems, and link workers’ extensive knowledge of the range of community support services available 14151617. Recent systematic reviews of non-clinical community interventions identified evidence, albeit weak, of a further range of patient benefits 1218.…”
Section: Is There Evidence That Social Prescribing Work?mentioning
confidence: 99%
“…Provide patients with a full explanation of the social prescribing programme offered. This has been found to help manage patient expectations of the service and increase their satisfaction15…”
Section: Social Prescribing In Practicementioning
confidence: 99%
“…There is emerging evidence that social prescribing activities can support people's mental health, with activities such as arts classes, gardening, and exercise schemes leading to increased empowerment, self-esteem, confidence, improved mental health outcomes and cognitive functioning, and lowered feelings of social exclusion and isolation [15][16][17]. Another social prescribing study found reductions in isolation and improvements in health-related behaviours and management of long-term conditions [18]. There is also growing evidence for the benefits of the common social prescribing 'model', that is, the referral from a GP, through a link worker, to community groups and activities.…”
Section: Introductionmentioning
confidence: 99%
“…We feel that the pilot would greatly benefit from multi-sectoral collaboration, especially with an aim to address complex health needs of deprived populations. In various coordinated care models around the world, it has often been achieved through collaboration between health care and social care (56,57). Furthermore, POZ Plus also entails a degree of functional integration in the form of selected support functions (a uniform IT system, management model, and reporting system), whose use is simply required by the government as the programme initiator and leader.…”
Section: Care Coordinationmentioning
confidence: 99%